2021
DOI: 10.3389/fcimb.2021.633905
|View full text |Cite
|
Sign up to set email alerts
|

Presence of L1014F Knockdown-Resistance Mutation in Anopheles gambiae s.s. From São Tomé and Príncipe

Abstract: Malaria, one of the most serious parasitic diseases, kills thousands of people every year, especially in Africa. São Tomé and Príncipe are known to have stable transmission of malaria. Indoor residual spraying (IRS) of insecticides and long-lasting insecticidal nets (LLIN) are considered as an effective malaria control interventions in these places. The resistance status of Anopheles gambiae s.s. from Agua Grande, Caue, and Lemba of São Tomé and Príncipe to insecticides, such as dichlorodiphenyltrichloroethane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Accordingly, the insecticide-induced selection pressure would allow those insects carrying resistance genes to survive insecticide treatment and pass on the resistance trait to their offspring, thereby driving an increase in the frequency of the resistance allele within the population over time [ 52 , 53 ]. The development of resistance against pyrethroids has been documented in various insects worldwide, including mosquito species such as Anopheles gambiae sensu stricto [ 54 ] and Anopheles arabiensis [ 55 ], as well as the house fly M. domestica [ 39 ]. In the present study, we confirmed the presence of the previously known kdr mutation L1014F, which was reported in the UAE in 2014, with our assays revealing its presence in most of the house fly populations tested in Abu Dhabi in 2023.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the insecticide-induced selection pressure would allow those insects carrying resistance genes to survive insecticide treatment and pass on the resistance trait to their offspring, thereby driving an increase in the frequency of the resistance allele within the population over time [ 52 , 53 ]. The development of resistance against pyrethroids has been documented in various insects worldwide, including mosquito species such as Anopheles gambiae sensu stricto [ 54 ] and Anopheles arabiensis [ 55 ], as well as the house fly M. domestica [ 39 ]. In the present study, we confirmed the presence of the previously known kdr mutation L1014F, which was reported in the UAE in 2014, with our assays revealing its presence in most of the house fly populations tested in Abu Dhabi in 2023.…”
Section: Discussionmentioning
confidence: 99%
“…albimanus populations from Guatemala, Ecuador, and Colombia [23]. On the other hand, speci c mutations at codons 1010, 1014 and 1014 in the kdr region have been associated with pyrethroid resistance [40]. In Peru, resistance to pyrethroids was reported in An.…”
Section: Discussionmentioning
confidence: 99%